"I've got to break the cycle for my son, so he doesn't go to juvie like his pops": Interrupting intergenerational patterns of incarceration. (24th June 2022) - VanderPyl, Taryn; Hernandez, Katelyn; Melchor‐Ayala, Omar
Abstract: Patterns of incarceration transmit generationally causing damage to families and communities across decades. Literature is replete with studies on the harmful impact of parental incarceration but is missing the voice of those living within this cycle. This study highlights the perspectives and lived experiences of those who have parents who have been incarcerated, are currently incarcerated themselves, and have children of their own. This middle generation sheds light on how and why they followed in their parents' footsteps and their desire to break this pattern for their own children. Implications and recommendations are discussed.